Design and Optimization of a Reconfigurable Intelligent Surface Using PIN and Varactor Diodes for 5G Communication - Chandachoriya A.; Panwar R.; Kumar A. (My University, 2025)
This article presents the design and analysis of a reconfigurable intelligent surface (RIS) for efficient electromagnetic (EM) wave manipulation. RIS performance is analyzed based on two distinct biasing configurations based on PIN and varactor diodes. A hybrid split-ring resonator (SRR) geometry forms the foundation of the proposed RIS, enabling dynamic control through integrated diodes. The study investigates the impact of these diodes on the reflection coefficient and phase shift, achieving a reflection coefficient of -2.2 dB and a phase shift of 180° at an operating frequency of 5.2 GHz. Key design parameters are analyzed to optimize performance, providing insights into the structure's frequency-dependent EM behavior and surface current distributions. The proposed RIS architecture is particularly suited for 5G wireless communication systems. © 2024 IEEE.